One of the water pollution sources at ciliwung river in Jakarta is domestic waste which from household who live in the long side ciliwung riverbank. The aim of the research are (1) to know characteristic of community who live in the long side ciliwung riverbank (2) to know the attitude of the community who live in the long side riverbank about waste disposal to the river, inpact of this and the program of clean river, (3) to know the community who live in the long side riverbank to carry out of - Agung Priambodo; Anna Fatchiya; Gatot Yulianto (Buletin Ekonomi Perikanan, 2006)
One of the water pollution sources at ciliwung river in Jakarta is domestic waste which from household who live in the long side ciliwung riverbank. The aim of the research are (1) to know characteristic of community who live in the long side ciliwung riverbank (2) to know the attitude of the community who live in the long side riverbank about waste disposal to the river, inpact of this and the program of clean river, (3) to know the community who live in the long side riverbank to carry out of disposal waste, (4) to know factors influence the attitude of the community who live in the long side riverbank factors to concem domestic waste (5) to know factors influence of the community who live in the long side riverbank to carry out of disposal waste (6) to know correlation between attitude with behave to carry out disposal waste The research used survey method and be analyzed with non parametric statistic. The research show the following, (1) attitude of the community who live in the long side riverbank about waste disposal to the river is neutral but about inpact and program of dean river are positive, (2) the community who live in the long side riverbank behave negative in cflSpOSal waste, (3) factors influence the altitude of the community who live in the long side riverbank to concern domestic waste are:· age, legality status, and the distance between their hose with the river, (5) correlation between attitude with behave to carry out disposal waste is negative.